PENGENALAN PROBIOTIK SEDERHANA UNTUK TERNAK AYAM KAMUPUNG DI DESA PERSIAPAN URSANA KECAMATAN INAMOSOL KABUPATEN SERAM BAGIAN BARAT - Wiesje Martha Horhoruw; Pieter Melianus Ririmasse (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2023)
Ursana Village is one of the preparatory hamlets for division into a village in Inamosol District. The most commonly kept livestock are cattle and native chickens. Constraints from the development of this farm, namely the lack of readiness, knowledge and skills of breeders. The potential development of free-range chicken has not been maximized. This is due to the lack of knowledge and motivation of the community in handling chicken diseases. Chicken disease is one of the risks that needs to be watched out for and faced with its own challenges in farming activities. Probiotics can increase livestock production when given regularly. The purpose of PKM is the application of probiotics to native chickens in disease prevention. This activity includes a social approach with the village government to take inventory of free-range chicken breeders for counseling, distribution of brochures to breeders or counseling participants, and demonstrations of making probiotics. Community service activities carried out in the Ursana Preparation Village increased the knowledge and skills of farmers regarding disease recognition and the manufacture of simple probiotics